The Inhibitory Effect of Curcumin Derivative J147 on Melanogenesis and Melanosome Transport by Facilitating ERK-Mediated MITF Degradation - Lv, Jinpeng; Yang, Ying; Jia, Bingyi; Li, Siqi; Zhang, Ximei; Gao, Rongyin (Frontiers in Pharmacology, 2021)
The therapeutic use of curcumin and chemically modified curcumin (CMC) for suppressing melanogenesis and tyrosinase activity have been recognized. J147 is a modified version of curcumin with superior bioavailability and stability. However, there is no report about the effects of J147 on pigmentation in vitro and in vivo. In our studies, we investigated the hypopigmentary effects of J147 treatment on melanocytes and explored the underlying mechanism. The present studies suggested that J147 suppressed both basal and α-MSH-induced melanogenesis, as well as decreased melanocyte dendricity extension and melanosome transport. J147 played these roles mainly by activating the extracellular signal-regulated protein kinase (ERK) pathway. Once activated, it resulted in MITF degradation and further down-regulated the expression of tyrosinase, TRP-1, TRP-2, Rab27a and Cdc42, ultimately inhibited melanin synthesis and melanosome transport. Furthermore, the hypopigmentary effects of J147 were demonstrated in vivo in a zebrafish model and UVB-induced hyperpigmentation model in brown guinea pigs. Our findings also suggested that J147 exhibited no cytotoxicity in vitro and in vivo. Taken together, these data confirmed that J147 may prove quite useful as a safer natural skin-whitening agent.